Outcome of Neonatal Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Evaluations, including MRI, MR angiography, and neuropsychological tests, at 1.5-8.4 years, of 8 infants after neonatal stroke involving the middle cerebral artery are reported from the University of Heidelberg, Mannheim, Germany.